EVALUASI SISTEM PENERIMAAN MURID BARU (SPMB) DI KOTA BANDAR LAMPUNG (STUDI PERBANDINGAN SMP NEGERI 2 BANDAR LAMPUNG DAN SMP NEGERI 45 BANDAR LAMPUNG) - Sukma Maulana; Eko Budi Sulistio; Dian Kagungan (Administrativa : Jurnal Birokrasi, Kebijakan dan Pelayanan Publik, 2026)
The implementation of the New Student Admission System (SPMB) in Bandar Lampung City under the Minister of Primary and Secondary Education Regulation Number 3 of 2025 still faces challenges in achieving equitable student distribution. This condition is reflected in the contrast between SMP Negeri 2 Bandar Lampung, which experiences high applicant interest, and SMP Negeri 45 Bandar Lampung, which remains under-enrolled despite having available capacity. This study aims to evaluate the implementation of the SPMB policy in Bandar Lampung City and to identify the supporting and inhibiting factors affecting its success. This research uses a descriptive qualitative approach through interviews, observation, and documentation. The data were analyzed using Stufflebeam's CIPP evaluation model consisting of context, input, process, and product evaluation. The findings show that, in the context aspect, SPMB emerged as a corrective policy to address disparities in the previous admission system, yet geographical boundaries and domicile administration still affect access, especially in border areas. In the input aspect, institutional reputation, facilities, human resources, and digital readiness shape school attractiveness and policy implementation. In the process aspect, online registration and verification have supported transparency, but server disruptions, invalid documents, and unequal digital literacy remain obstacles. In the product aspect, SPMB has improved access through domicile and affirmation pathways, but equal distribution of students between schools has not been fully achieved. Therefore, SPMB requires stronger socialization, more reliable digital infrastructure, equalization of school facilities, and special policy arrangements for border-area schools.